"Speech Is Golden": The Importance of Colloquial Arabic for Reading Standard Arabic for Beginning Readers. - Rakhlin, Natalia V.; Nan Li; Aljughaiman, Abdullah; Grigorenko, Elena L. (Journal of Speech, Language & Hearing Research)
Purpose: We investigated the role of spoken language in the acquisition of literacy in the context of Arabic diglossia, where the written language, Standard Arabic, deviates substantially from the spoken language, Colloquial Arabic, children acquire naturally from birth. Method: The participants (N = 110; 40 girls) were Saudi Arabic--speaking children in Grades 2-4. Children completed assessments of oral paragraph reading and word decoding using a vowelized script. They also completed three spoken assessments of Colloquial Arabic, which include sentence comprehension, sentence completion, and pragmatic knowledge, as well as a test of phonological awareness. We used path analysis to investigate the contributions of each of the spoken language indicators, decoding, and phonological awareness to reading comprehension (RC) in single and multiple serial mediator models. Results: We found that spoken language (i.e., sentence comprehension, sentence completion, and pragmatic knowledge) and word decoding uniquely contributed to RC. Moreover, word decoding mediated the association between spoken language and RC. The path from spoken language to phonological awareness, then to word decoding, and finally to RC was inconclusive. Conclusions: While most studies on literacy acquisition in the context of Arabic diglossia focus on the linguistic distance between the colloquial (spoken) and the standard (written) language varieties, our results highlight the important contribution of spoken language skills to reading skills in Arabic despite this linguistic gap. The important implication of these findings is that spoken language interventions aimed at boosting children's narrative language skills in their home language (Colloquial Arabic) are an important tool for building a foundation for literacy in diglossia contexts.